2010
DOI: 10.1111/j.1750-3639.2010.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal MCP‐1 Mediates Microglia Recruitment and Neurodegeneration Induced by the Mild Impairment of Oxidative Metabolism

Abstract: Chemokines are implicated in the neuroinflammation of several chronic neurodegenerative disorders. However, the precise role of chemokines in neurodegeneration is unknown. Thiamine deficiency (TD) causes abnormal oxidative metabolism in the brain as well as a well-defined microglia activation and neurodegeneration in the submedial thalamus nucleus (SmTN), which are common features of neurodegenerative diseases. We evaluated the role of chemokines in neurodegeneration and the underlying mechanism in a TD model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
92
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 75 publications
3
92
0
Order By: Relevance
“…MCP-1 causes microglia recruitment/activation to produce cytokines and exacerbates neurodegeneration. 96 Our data showed that the rotenone-induced elevation in striatal MCP-1 decreased after treatment with cerebrolysin. Cerebrolysin, thus, might exert its neuroprotective action, at least in part, by preventing the release of MCP-1 during inflammation.…”
mentioning
confidence: 50%
“…MCP-1 causes microglia recruitment/activation to produce cytokines and exacerbates neurodegeneration. 96 Our data showed that the rotenone-induced elevation in striatal MCP-1 decreased after treatment with cerebrolysin. Cerebrolysin, thus, might exert its neuroprotective action, at least in part, by preventing the release of MCP-1 during inflammation.…”
mentioning
confidence: 50%
“…Consistently, neural MCP-1 in the brain has been reported to mediate microglia recruitment and activation that exacerbates neurodegeneration. 22 Lack of this upregulation in ASK1 KO mice suggested that the microglia were not navigated effectively to the injury site in these mice. Pharmacological inactivation of ASK1 or p38 suppressed LPS-induced TNFa and LPS/TNFa-induced iNOS productions in microglia (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that microglia, the resident immune cells in the central nervous system (CNS), may be considered the main mediators of inflammation-associated disorders. These cells manage the innate and adaptive immune responses in various pathological processes including brain trauma, ischemia, stroke and infections, as well as during CNS repair (Graeber and Streit 2010;Yang et al 2011). It has been observed that active microglia can clear Received September 29, 2015; revised manuscript received November 16, 2015; accepted November 17, 2015.…”
Section: Introductionmentioning
confidence: 99%